PENGARUH AUDIT TENURE, FEE AUDIT DAN SPESIALIS AUDITOR TERHADAP KUALITAS AUDIT - Berkah Sawaludin; Fina Fitriyana (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of audit tenure, audit fee, and auditor specialization on audit quality in the food and beverage industry listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The sampling method used in this study is purposive sampling, with a quantitative research approach. The data utilized is secondary data, specifically the companies' annual financial reports. The sample consists of 17 food and beverage industry companies, observed over a period of five years, resulting in 85 observation objects. The analytical technique employed includes descriptive statistical analysis and logistic regression analysis, using the eViews version 12 application as a supporting tool. The findings indicate that audit tenure has a negative effect on audit quality, while audit fee and auditor specialization have no significant impact on audit quality